Experimental Study on the Characterization of Aging Resistance Properties of Optical Cables in the Hydrogen-Containing Downhole Environment - Xu, Feng; Li, Litong; Jing, Peng; Yu, Zhiwei; Zhang, Jialiang; Liu, Shuhui (Sensors (Basel, Switzerland), 2024)
The utilization of downhole optical cables has significantly enhanced the efficiency and reliability of oilfield production operations; however, the challenging high-temperature and high-pressure conditions prevalent in oil-gas fields markedly reduce the service lifespan of these optical cables. This limitation severely impedes their application and further development in subterranean environments. In this study, a qualitative analysis was conducted on the structural materials utilized in two types of optical cables to identify these materials and assess the high-temperature tolerance and aging resistance properties of the optical fibers incorporated within. It was discovered that hydrogen infiltration into the subterranean optical cables predominantly accounts for their operational failure. To address this issue, an optical loss testing platform was established, facilitating the execution of a high-temperature and high-pressure hydrogen permeation aging experiment on the optical fibers, allowing for the evaluation of the hydrogen resistance capabilities of the two types of optical fibers. The findings from this study provide a theoretical foundation and methodological guidance for the optimization of optical fibers, aiming to enhance their durability and functional performance in adverse environmental conditions encountered in oil-gas field applications.